Elastodynamic analysis of thick multilayer composite plates by the Boundary Element Method (2015)
Dynamic stress analysis of laminated composites plates represents a relevant task in designing of aerospace, shipbuilding and automotive components where impulsive loads can lead to sudden structural failure. The mechanical complexity inherent to these kind of components makes the numerical modeling an essential engineering analysis tool. This work deals with dynamic analysis of stresses and deformations in laminated composites thick plates using a new Boundary Element Method formulation. Composite laminated plates were modeled using the Reissner's plate theory. We propose a direct time-domain formulation based on elastostatic fundamental solution for symmetrical laminated thick plates. Formulation takes into account the rotational inertia of the plate. Domain integrals related to distributed body forces and those related to inertial terms are evaluated using the Radial Integration Method. Contour integrals are numerically evaluated using quadratic approximation for displacements and generalized forces. Time integration is performed using the Houbolt Integration Method. Resulting shear forces and bending moments are calculated. The results obtained using this formulation show good agreement when compared with finite element solutions. Copyright © 2015 Tech Science Press.